Tangduqing Granules Attenuate Insulin Resistance and Abnormal Lipid Metabolism through the Coordinated Regulation of PPARγ and DGAT2 in Type 2 Diabetic Rats - Qinghua Zhang; Yingying Huang; Xiaojin Li; Hongyi Liu; Baichuan He; Bin Wang; Yuntao Ma; Xiang Zhou; Yaqin Liu; Shentao Wu (Journal of Diabetes Research)
Insulin resistance (IR) is a vital hallmark of type 2 diabetes mellitus, which is characterized by an impaired ability of insulin to promote glucose uptake and utilization. Lipid deposition is closely associated with impaired insulin sensitivity. PPARγ plays an important role in glucose homeostasis, adipocyte differentiation, and insulin sensitivity. Likewise, DGAT2 also exerts a crucial role in integrating carbohydrate and lipid metabolism in the liver. The present study is aimed at evaluating a Chinese medicinal formula, Tangduqing granules (TDQ), with multifaceted actions against lipid and glucose metabolism disorder and IR of type 2 diabetes. An animal model of type 2 diabetes was developed by high-fat diet feeding plus low-dose streptozotocin injection. After oral administration of TDQ for 5 weeks, the effects on glucose and lipid metabolism and the underlying mechanism were evaluated by biochemical, histological, RT-PCR, and western blotting methods. The results showed that TDQ decreased fasting blood glucose, ameliorated glucose tolerance, and improved IR. Besides, TDQ regulated hyperlipidemia symptoms, decreased serum lipid levels and liver TG, and reduced hepatic steatosis in a type 2 diabetic rat model. Furthermore, TDQ reversed diabetes-induced decrease in the mRNA and protein expression of PPARγ and elevation in the mRNA and protein levels of DGAT2 in the liver. In addition, we showed that interference of TDQ ameliorated palmitate-induced glucose and lipid metabolic abnormalities in HepG2 cells. TDQ are, therefore, a potential Chinese medicinal formula that relieves IR and lipid metabolism disorder might be through promotion of PPARγ and decrease of DGAT2 expression.